2015
DOI: 10.3390/nu7085324
|View full text |Cite
|
Sign up to set email alerts
|

Apple Polyphenols Decrease Atherosclerosis and Hepatic Steatosis in ApoE−/− Mice through the ROS/MAPK/NF-κB Pathway

Abstract: In this study, we examined the effects of apple polyphenols (APs) on hyperlipidemia, atherosclerosis, hepatic steatosis and endothelial function and investigated the potential mechanisms. ApoE−/− mice were fed a western-type diet and orally treated with APs (100 mg/kg) or atorvastatin (10 mg/kg) for 12 weeks. Hyperlipidemia and atherosclerosis in the aortic sinuses and, and hepatic lipidosis were measured. The treatment with APs or atorvastatin induced a remarkable reduction in the atherosclerotic lesions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 43 publications
10
60
0
Order By: Relevance
“…In this study, our results showed that APPs significantly increased the mRNA expressions of hepatic CAT , GST and SOD1 mRNA levels in weaned piglets. Our data also showed that the serum MDA content of weaned piglets was significantly decreased by APPs, which was consistent with the results in rodents (Ogino et al, ; Xu et al, ). Together, the results above suggested that dietary APPs supplementation enhanced antioxidative status in liver and serum.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, our results showed that APPs significantly increased the mRNA expressions of hepatic CAT , GST and SOD1 mRNA levels in weaned piglets. Our data also showed that the serum MDA content of weaned piglets was significantly decreased by APPs, which was consistent with the results in rodents (Ogino et al, ; Xu et al, ). Together, the results above suggested that dietary APPs supplementation enhanced antioxidative status in liver and serum.…”
Section: Discussionsupporting
confidence: 93%
“…We found that dietary APPs supplementation had no effect on growth performance, which is consistent with previous reports (Manzano et al, ; Nakazato et al, ; Yoshida et al, ). On the contrary, some other investigations based on mouse model of hyperlipidaemia or rats fed cholesterol showed different response patterns (improvement or decrease in growth performance; Osada et al, ; Xu et al, ). The reason might be the discrepancies in the experimental animal or energy level of diets.…”
Section: Discussionmentioning
confidence: 95%
“…Similar activations have been reported in response to apple pomace (Sharma et al, ) and green tea (Na & Surh, ) consumption, as well as from other fruits and vegetables (Orena et al, ). Nonetheless, activation of other signaling pathways could have been involved, such as mitogen activated protein kinases (Beltrán‐Debón et al, ; Xu et al, ) to ameliorate adipose inflammation and dysfunction of hepatocytes during NASH development.…”
Section: Discussionmentioning
confidence: 99%
“…The existed evidence certifies that MAPK may activate NF-κB [44]. NF-κB activation regulates the generation of mediators resulting in the thrombotic potential of human atherosclerotic plaques, such as tissue factor, matrix metalloproteinases and inflammatory cytokines [45].…”
Section: Discussionmentioning
confidence: 99%